Comparing the first provisional administrations in Tunisia and Libya: some tentative conclusions. Issue 2 (4th March 2019) - Henneberg, Sabina
ABSTRACT: This article compares the actors, institutions and strategies of the first Tunisian Provisional Administration (TPA), which was in place from the departure of authoritarian President Ben Ali until the elections for a National Constituent Assembly, with those of the Libyan National Transition Council (NTC), in place from the start of authoritarian collapse to the first post-uprising elections. The two first provisional administrations exhibited important differences. Key actors in the TPA were 'soft-liners' from the old regime and a network of civil society actors, while in the NTC armed groups soon became the most important actors. Functioning state institutions also permitted the TPA to carry out its work more effectively. Finally, the two provisional administrations deployed very different strategies, with the TPA operating on a basis of dialogue and consensus while the NTC often struggled to reach collective decisions. The paper argues that, while many of the differences between the two first provisional administrations can be traced back to different historical and structural influences and these channeled actors' decisions, the first provisional administrations nonetheless had opportunities to shape later phases of change.